Correction: The Terezita Romo Papers: Capturing the Spirit of Collective Action in Archives. Issue 1 (5th November 2019) - Ulinskas, Moriah
This article details corrections to the article:Ulinskas, M., 2018 . The Terezita Romo Papers: Capturing the Spirit of Collective Action in Archives. KULA: knowledge creation, dissemination, and preservation studies, 2(1), p. 4. DOI:http://doi.org/10.5334/kula.22